Arrangement of Makassar City Water Sports Tour Packages based on Geographic Information Systems - Zulkifli Harahap; Enos Julvirta; Yayan Dian F.; Muh. Musawantoro; Darsyaf Hadi W. (Politeknik Pariwisata Makassar, Indonesia, 2022)
This study aims to model the Tirta Tour package in Makassar City. This research method uses a qualitative approach, the data sources are obtained through surveys with field notes, interviews and documentation, while the data processing techniques use the help of ArcGIS 10.5 software. The data collection techniques used in this study are: Focus Group Discussion (FGD), interviews, study comparison and literature study were used for qualitative data. Based on the processed data, it was found as follows: 1) Water tourism potential in Makassar City as a result of analysis 3A: Accessibility, Amenity and Activities in general, the cluster of islands in the Spermonde Archipelago has the potential to become superior marine tourism with current conditions it can be said to be natural. heritage landscapes. 2) Mapping model for Tirta Tour Packages in Makassar City in the form of Tirta Travel Routes with a Stopover Movement Pattern with 4 Tourist Attractions. This study recommends the preparation of an online water tourism information system for Makassar City so that it can be accessed anytime and anywhere.